Reducing green characters in Cabernet Sauvignon - Wilkinson, Kerry; Kennedy, Ursula; Pierce, Kieran; Gibberd, Mark (Australian Wine Industry Technical Conference Inc, 2007)
Viticultural and oenological approaches to reduce 3-isobutyl-2-methoxypyrazine (IBMP) concentrations in wine are discussed. Variation in vine vigour and crop yield were found to be correlated with wine IBMP concentrations. Fruit derived from high vigour vines yielded between 2- and 4-fold higher wine IBMP concentrations than fruit derived from low vigour vines. When a 50% crop thinning treatmentwas applied to low vigour vines, no effect on wine IBMP content was observed. However, the same treatment resulted in a 1.3-fold higher concentration of IBMP when applied to high vigour vines. Trials were conducted to evaluate the capacity of commercial yeast strains to reduce IBMP levels during fermentation. Wines fermented with CSM and ICV-D21 yeasts had slightly lower IBMP levels than wines fermented with E C1118. No significant differences in sensory attributes between wines were apparent.